2019
DOI: 10.1002/cmdc.201900112
|View full text |Cite
|
Sign up to set email alerts
|

Sulfide Analogues of Flupirtine and Retigabine with Nanomolar KV7.2/KV7.3 Channel Opening Activity

Abstract: The potassium channel openers flupirtine and retigabine have proven to be valuable analgesics or antiepileptics. Their recent withdrawal due to occasional hepatotoxicity and tissue discoloration, respectively, leaves a therapeutic niche unfilled. Metabolic oxidation of both drugs gives rise to the formation of electrophilic quinones. These elusive, highly reactive metabolites may induce liver injury in the case of flupirtine and blue tissue discoloration after prolonged intake of retigabine. We examined which … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 41 publications
3
23
0
Order By: Relevance
“…In agreement with this hypothesis, our results also highlight that changes in lipophilicity at C-5 also modify the kinetics of onset and offset of Kv7.2 channel activation; in fact, when compared to RET (log P = 3.08), more lipophilic 23a (log P = 6.83) and 24a (log P = 5.58) both displayed slower kinetics. These results are in good agreement with recently published studies concerning FLU analogues . Most importantly, we found that the type of substituents in position C-5 of the indole series influences selectivity between Kv7.2 and Kv7.3 channels.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with this hypothesis, our results also highlight that changes in lipophilicity at C-5 also modify the kinetics of onset and offset of Kv7.2 channel activation; in fact, when compared to RET (log P = 3.08), more lipophilic 23a (log P = 6.83) and 24a (log P = 5.58) both displayed slower kinetics. These results are in good agreement with recently published studies concerning FLU analogues . Most importantly, we found that the type of substituents in position C-5 of the indole series influences selectivity between Kv7.2 and Kv7.3 channels.…”
Section: Discussionsupporting
confidence: 93%
“…In agreement with experience made with previously prepared analogues of flupirtine and retigabine bearing different scaffolds, an exchange of the carbamate function for an amide group was possible without drastically impairing the activity [24,33] . This was confirmed by molecular docking since the hydrogen bonds of the carbamate group of flupirtine and retigabine are preserved for amide derivatives (Figure 3C/D).…”
Section: Resultssupporting
confidence: 88%
“…A replacement of the primary amino function with a methyl group or other non‐polar substituents along with additional structural changes generally led to more lipophilic compounds as reflected by higher log D 7.4 values throughout all N‐1/3 dicarba analogues compared to flupirtine and retigabine (Table 1). A possible correlation between increased lipophilicity and improved activity was already observed in our previous work but could not be clearly proven since other structural features aside from the compound lipophilicity also affect the activity [33] . Nevertheless, lipophilicity seems to be a relevant variable influencing activity, and a possible reason might be the location of the K V 7.2/3 binding site, which is situated in the area where the channel is embedded in the cell membrane.…”
Section: Resultsmentioning
confidence: 72%
“…Our study in an animal model and clinical studies suggest that seizures resolve within 4–5 days of onset following neonatal hypoxia-ischemia ( 25 , 39 ), therefore, is less likely that flupirtine will be used as antiseizure medication in neonates for a prolonged period of time. However, efforts are underway to develop more potent analogues of flupirtine that are devoid of such side-effects ( 40 ).…”
Section: Discussionmentioning
confidence: 99%